The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0144720
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Thalamocortical Sleep Oscillations Are Important for Memory Consolidation in Humans

Abstract: Sleep, specifically non-rapid eye movement (NREM) sleep, is thought to play a critical role in the consolidation of recent memories. Two main oscillatory activities observed during NREM, cortical slow oscillations (SO, 0.5–1.0Hz) and thalamic spindles (12–15Hz), have been shown to independently correlate with memory improvement. Yet, it is not known how these thalamocortical events interact, or the significance of this interaction, during the consolidation process. Here, we found that systemic administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(147 citation statements)
references
References 35 publications
11
135
1
Order By: Relevance
“…Recent work has begun to integrate formerly independent lines of research on sleep SO and spindle activity, suggesting that their interplay might be critical for sleep‐related memory consolidation (Helfrich et al., ; Molle & Born, ; Niknazar, Krishnan, Bazhenov, & Mednick, ). Our work supports this notion by replicating the distinct temporal interaction of SO and spindle activity in the cortical up‐state and its correlation with declarative memory consolidation in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has begun to integrate formerly independent lines of research on sleep SO and spindle activity, suggesting that their interplay might be critical for sleep‐related memory consolidation (Helfrich et al., ; Molle & Born, ; Niknazar, Krishnan, Bazhenov, & Mednick, ). Our work supports this notion by replicating the distinct temporal interaction of SO and spindle activity in the cortical up‐state and its correlation with declarative memory consolidation in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…While we found network states dominated by either spindles or slow oscillations, under certain conditions (such as only moderate reduction of the ACh level) we also observed mixed states combining these two major rhythms. Such mixed states may occur in vivo under normal conditions (Aeschbach and Borbely, 1993; Muller et al, 2006); our recent behavior study suggests that the strengths of the phase amplitude coupling between the spindle and the slow oscillation during NREM sleep correlates with memory consolidation (Niknazar et al, 2015). We speculate that the mixed states may become prevalent in some pathological conditions such as in Alzheimer’s disease where sleep is altered and changes to the neuromodulatory system are reported (Wulff et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We focused on Stage 2 sleep because sleep spindles are most prominent during this stage, also, prior studies have shown that sleep coordination between spindles and SOs during Stage 2 (as compared to slow wave sleep) may have a specific memory benefit (Niknazar et al, 2015).…”
Section: Electrophysiological Datamentioning
confidence: 99%